2010
DOI: 10.1177/1461444810365311
|View full text |Cite
|
Sign up to set email alerts
|

The medium is the joke: online humor about and by networked computers

Abstract: This article explores the uncharted territory of reflexive internet humor about networked computers. A combined quantitative-qualitative analysis of 250 texts sampled from popular websites yielded a map of the main themes underpinning this massive corpus of humor. We analyzed them in relation to three grand theories of the nature of humor -superiority, release, and incongruity -locating each theme on a matrix deriving from the theories: (i) a superiority axis, running between the powerful and weak players in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
0
13
0
1
Order By: Relevance
“…Even though humor use in traditional forms of media has been relatively well studied, particularly in advertising, the digital media realm is still ripe for exploration (Shifman & Blondheim, 2010). Indeed, the majority of Americans now turn to the Internet to seek information about science (National Science Board, 2018).…”
Section: Social Media Engagementmentioning
confidence: 99%
“…Even though humor use in traditional forms of media has been relatively well studied, particularly in advertising, the digital media realm is still ripe for exploration (Shifman & Blondheim, 2010). Indeed, the majority of Americans now turn to the Internet to seek information about science (National Science Board, 2018).…”
Section: Social Media Engagementmentioning
confidence: 99%
“…There have also been studies that code the content of messages to determine their impact on diffusion. Research has found that humor is one of the elements that can help content spread (Kirby & Marsden, ; Shifman & Blondheim, ), and content analysis of tweets labeled as “novel” are more likely to be retweeted (Petrovic, Osborne, & Lavrenko, ; Uysal & Croft, ). Messages labeled as having a positive emotion are more likely to spread (Kim & Yoo, ; Stieglitz & Dang‐Xuan, ), as are messages that “resonate” with the audience (Asur & Huberman, ).…”
Section: Literaturementioning
confidence: 99%
“…Literature addresses these decision phases by looking at properties of the content , by sender/receiver motivations and by network structure . From the content perspective, researchers have identified the following influences on the decision to consume and share information: emotional appeal [20, 21], resonance [22], humor [23, 24], salience [25, 26] and usability [27]. …”
Section: Theory Developmentmentioning
confidence: 99%